Nonrandom minichromosome replication in Escherichia coli K-12. - Koppes, L J (1987)
The intervals between rounds of chromosome and minichromosome replication were measured by density shift experiments and found to be similar. Thus the minichromosome, a lambda asnA oriC bacteriophage, mostly replicates once each division cycle rather than randomly, despite its high copy number. Slight differences between the chromosome and the oriC plasmid are explained.